Comparative assessment of 2D photogrammetry versus direct anthropometry in nasal measurements - Afaq, Shehzeen; Jain, S.K.; Sharma, Nidhi; Sharma, Sonika (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The nose significantly influences facial aesthetics, necessitating a comprehensive understanding of na sal anatomy and facial aesthetics standards for successful rhinoplasty. This study investigates the reliability and precision of two-dimensional photogrammetry compared to direct measurements for nasal anthropometry. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This cross-sectional study was carried out at Teerthanker Mahaveer Medical College and Research Cen ter, Moradabad which included 640 volunteers from six zones of the Indian population. Direct anthropometry and 2D photo grammetry were the two methods used to evaluate each parameter. A caliper was employed for direct anthropometry, and software analysis of nasal characteristics was used for the indirect 2D technique. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The result revealed significant gender-based differences in all nasal dimensions assessed by direct measurements, with the exception of the length of the nasal bridge. In contrast, 2D photogrammetry demonstrated no significant variation in ana tomical nasal width and nasal bridge length across the genders. Of the eight nasal parameters analyzed, five parameters (nose height, morphological nose width, alar length, nasal tip protrusion, and nasal index) exhibited excellent reliability. Nasal bridge length and columellar length showed moderate reliability of 2D photogrammetry. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. This research reveals gender-based differences in nasal dimensions, with males generally having larger dimensions. It suggests 2D photogrammetry as a reliable alternative to direct anthropometry for specific nasal measurements, offering practical benefits in clinical and aesthetic applications. However, it has limitations, such as moderate reliability in measuring nasal bridge length and Columellar length, underscoring the necessity for cautious interpretations for specific parameters. Further research is recommended to improve precision and applicability, while addressing limitations like sensitivity to imaging distortion and also incorporating the 3D technique to enhance the robustness of the methodology; the absence of 3D is a benchmark.